Diagnosis and treatment of oral lichen sclerosus in a pediatric patient - Simonato, Luciana Estevam; Tomo, Saygo [UNESP]; Pereira, Débora Lima; de Almeida, Oslei Paes; Vargas, Pablo Agustin; Miyahara, Glauco Issamu [UNESP] (Wiley, 2019)
Lichen sclerosus is an uncommon chronic inflammatory disease, which rarely affects the oral mucosa. Here, we describe the occurrence of oral lichen sclerosus with gingival destruction in a 12-year-old female patient. After diagnostic confirmation by histopathology, intralesional injection of corticosteroid was performed, producing satisfactory remission of the lesion.
Keywords: autoimmune diseases; gingival recession; lichen sclerosus et atrophicus; oral lichen sclerosus